MODIFIKASI MARSHALL DALAM PERENCANAAN CAMPURAN ASPAL PORUS UNTUK CEMENT TREATED ASPHALT MIXTURE (CTAM) - R. Anwar Yamin; Bambang Ismanto Siswosubrotho (Jurnal Jalan-Jembatan, 2002)
In the line with increment of crude oil price and demand impovement of oil cause id a raisting the asphalt price. In this time, the unit price of asphalt mixtrure is not more relevant and higher than concrete's unit price. Cement Treated Asphalt Mixtures (CTAM) is one of solutions for reducing the use of asphalt. Basically, CTAM is a porous asphalt mix which it voids filled cement mortar. For those, voids in mix of porous asphalt and characteristics of cement mortar are two parameters which should be considered in making CTAM. This paper just concerned to design procedure in porus asphalt for CTAM's purpose. The result of this study shown that Marshall procedure which had modified could be used for this purpose. The modification done in this study only on the sample's preconditoning procedure prior testing i.e. by conductingn oven heating on temperature 50oC for 110 minutes.